2015
DOI: 10.1111/fcsr.12131
|View full text |Cite
|
Sign up to set email alerts
|

Education Fever: Exploring Private Education Consumption Motivations Among Korean Parents of Preschool Children

Abstract: Education fever, the national obsession with the attainment of education in Korea, has received attention from the media and researchers. However, research on Korean parents’ investment in private education for their preschool children is limited. The purpose of this study was to explore what the consumption of private education means to Korean parents, and to identify factors motivating their consumption behavior. Focus group interviews with 23 Korean mothers of preschool children were conducted to identify w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A longitudinal study in the United States showed that 78.4% of children of those studied had participated in one or more types of after-school tutoring during kindergarten and first grade, among which sports were the most popular, while music and arts were the least popular [2]. The results of studies in regions such as South Korea, Singapore, Canada, and Hong Kong, China were all similar [3][4][5][6]. The "Annual Report on Chinese Children's Development (2020)" pointed out that nearly 90% of preschool children in China's urban areas had participated in after-school tutoring.…”
Section: Introductionmentioning
confidence: 92%
“…A longitudinal study in the United States showed that 78.4% of children of those studied had participated in one or more types of after-school tutoring during kindergarten and first grade, among which sports were the most popular, while music and arts were the least popular [2]. The results of studies in regions such as South Korea, Singapore, Canada, and Hong Kong, China were all similar [3][4][5][6]. The "Annual Report on Chinese Children's Development (2020)" pointed out that nearly 90% of preschool children in China's urban areas had participated in after-school tutoring.…”
Section: Introductionmentioning
confidence: 92%
“…For example, the earnings ratio of tertiary graduates to lower secondary graduates in Korea decreased from 217.0 per cent in 2005 to 172.9 per cent in 2021 (OECD 2022b). Second, although Korean parents participated in severe education competitions for their children, nearly half of Korean households already reported their private education expenditure as a massive financial burden for household livelihoods (Woo and Hodges 2015). Third, this education fever also had serious negative effects on the psychological condition of students, and it sometimes discouraged study motivation (Woo and Hodges 2015; OECD 2021).…”
Section: Education and Economic Crises In Koreamentioning
confidence: 99%
“…Second, although Korean parents participated in severe education competitions for their children, nearly half of Korean households already reported their private education expenditure as a massive financial burden for household livelihoods (Woo and Hodges 2015). Third, this education fever also had serious negative effects on the psychological condition of students, and it sometimes discouraged study motivation (Woo and Hodges 2015; OECD 2021). Lastly, it has been regarded as an important factor in low fertility rates in East Asian region including Korea because this excessive education arm races tend to significantly suppress child‐care willingness in this region (Jones 2019).…”
Section: Education and Economic Crises In Koreamentioning
confidence: 99%
“…Korean society is considered one of the most competitive, and education is highly valued, where a large focus is placed on entering prestigious schools-credentialism (Woo & Hodges, 2015). Korea's competitive environment shapes the way parents, most often mothers, raise their children, resulting in excessive educational enthusiasm-parenting ideologies.…”
Section: Education and Parenting: Being A Japanese Mother In Koreamentioning
confidence: 99%